IQ, Expectations, and Choice - Francesco D'Acunto; Daniel Hoang; Maritta Paloviita; Michael Weber (Bank of Finland, 2019)
We use administrative and survey-based micro data to study the relationship between cognitive abilities (IQ), the formation of economic expectations, and the choices of a representative male population. Men above the median IQ (high-IQ men) display 50% lower forecast errors for inflation than other men. The inflation expectations and perceptions of high-IQ men, but not others, are positively correlated over time. High-IQ men are also less likely to round and to forecast implausible values. In terms of choice, only high-IQ men increase their propensity to consume when expecting higher inflation as the consumer Euler equation prescribes. High-IQ men are also forward-looking - they are more likely to save for retirement conditional on saving. Education levels, income, socio-economic status, and employment status, although important, do not explain the variation in expectations and choice by IQ. Our results have implications for heterogeneous-beliefs models of household consumption, saving, and investment.
URN:NBN:fi:bof-201901181038
Keywords: D12; D84; D91; E21; E31; E32; E52; E65; 330